A molecular self-assembled colourimetric chemosensor array for simultaneous detection of metal ions in water. Issue 49 (2nd June 2017) - Sasaki, Yui; Minamiki, Tsukuru; Tokito, Shizuo; Minami, Tsuyoshi
Abstract : An easy-to-prepare chemosensor assay based on molecular self-assemblies of 3-nitrophenylboronic acid and catechol dyes can detect metal ions qualitatively and quantitatively. Abstract : We propose a novel strategy for a high-throughput sensing of metal ions using a molecular self-assembled colourimetric chemosensor array. The proposed colourimetric assay has been achieved by only using the combination of commercially available materials. Importantly, the easy-to-prepare assay can be utilised to quantitatively detect metal ions under competitive conditions.